2013
DOI: 10.1038/srep01272
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of a highly spin-polarized organic spinterface at room temperature

Abstract: Organic semiconductors constitute promising candidates toward large-scale electronic circuits that are entirely spintronics-driven. Toward this goal, tunneling magnetoresistance values above 300% at low temperature suggested the presence of highly spin-polarized device interfaces. However, such spinterfaces have not been observed directly, let alone at room temperature. Thanks to experiments and theory on the model spinterface between phthalocyanine molecules and a Co single crystal surface, we clearly evidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
91
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 38 publications
8
91
1
Order By: Relevance
“…with a flat ring structure) π-conjugated molecules have been studied. In particular, metal-phthalocyanines (Pc's) and porphyrins have received a considerable amount of attention [89,93,96,97,99,[103][104][105]107]. The metal ions in these metallo-organic molecules typically have unpaired spins, which are found to couple to the ferromagnetic substrate via the exchange interaction.…”
Section: Spin Dependent Effects At Hybrid Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…with a flat ring structure) π-conjugated molecules have been studied. In particular, metal-phthalocyanines (Pc's) and porphyrins have received a considerable amount of attention [89,93,96,97,99,[103][104][105]107]. The metal ions in these metallo-organic molecules typically have unpaired spins, which are found to couple to the ferromagnetic substrate via the exchange interaction.…”
Section: Spin Dependent Effects At Hybrid Interfacesmentioning
confidence: 99%
“…This has been studied in some detail for various π-conjugated molecules adsorbed on ferromagnetic surfaces. The most common experimental techniques to probe the interface electronic and magnetic structure are x-ray magnetic circular dichroism (XMCD) [93][94][95], spin-polarized scanning tunneling microscopy (SP-STM) [90,[96][97][98], spin-polarized metastable de-excitation spectroscopy(SP-MDS) [99][100][101], spin-polarized ultraviolet photoelectron spectroscopy (SP_UPS) [102][103][104], and spin-resolved two-photon photoemission (SR-2PPE) [77]. Modeling is typically done with density functional theory (DFT) [89,95,97,98,[104][105][106][107][108][109].…”
Section: Spin Dependent Effects At Hybrid Interfacesmentioning
confidence: 99%
“…Photoemission spectroscopy or scanning tunneling microscopy, combined with first-principles calculations, enable a detailed analysis of the spin-dependent electronic properties of metal-organic interfaces. Bonding between a molecule and a ferromagnetic metal leads to spin-split (anti)bonding states and induces a spin polarization that extends onto the molecule [138,139,140,141,157,175,14,142]. For instance, calculations on C 60 |Fe(001) interfaces yield a magnetic moment of 0.2 µ B induced on the C 60 molecules [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that highly spin-polarized currents in spintronic devices may be obtained by exploiting the spin-dependent interaction between molecular materials and ferromagnetic electrodes, which has been coined "spinterface science" [137]. The spin-dependent electronic structure of metal-organic interfaces is accessible through photoemission spectroscopy, scanning tunneling microscopy (STM), and first-principles calculations [138,139,140,141,14,142].…”
Section: Introductionmentioning
confidence: 99%
“…At the interface between the materials phenomena like orbital hybridisation and charge transfer can greatly influence the transport of spins across the interface. Spin polarised microscopy and spectroscopy techniques have shown these effects to be typically spin dependent, resulting in a hybrid interface with magnetic properties that are quite different from those of the bulk ferromagnet (Djeghloul et al, 2013;Lach et al, 2012;Rizzini et al, 2014;Sun et al, 2014;Suzuki et al, 2002Suzuki et al, , 2004Tran et al, 2013). It is a topic of active study how this effects the spin transport across the interface Kawahara et al, 2012;Raman et al, 2013;Schmaus et al, 2011;Steil et al, 2013).…”
mentioning
confidence: 99%